Targeted Modification of a Novel Amphibian Antimicrobial Peptide from Phyllomedusa tarsius to Enhance Its Activity against MRSA and Microbial Biofilm - Gao, Yitian; Wu, Di; Wang, Lei; Lin, Chen; Ma, Chengbang; Xi, Xinping; Zhou, Mei; Duan, Jinao; Bininda-Emonds, Olaf R. P.; Chen, Tianbao; Shaw, Chris (Frontiers in Microbiology, 2017)
Antimicrobial peptides (AMPs) in the skin secretions of amphibians are fundamental components of a unique defence system that has evolved to protect these hosts from microbial invasion. Medusins constitute a recently-discovered AMP family from phyllomedusine leaf frog skin and exhibit highly-conserved structural characteristics. Here, we report a novel medusin, medusin-PT, from the skin secretion of the Tarsier Leaf Frog, Phyllomedusa tarsius. The mature peptide was initially identified from its cloned biosynthetic precursor-encoding cDNA as obtained by the rapid amplification of cDNA ends (RACE) method. Reverse-phase HPLC and tandem mass spectrometry confirmed both the presence of medusin-PT in the skin secretion and its primary structure. In a range of bioassays, medusin-PT exhibited antimicrobial activity against only the Gram-positive bacterium Staphylococcus aureus at 64 μg/ml. However, after directed changes to enhance the cationicity and amphipathicity of the peptide structure, three analogues showed more potent antimicrobial activity against several additional bacteria including the antibiotic-resistant bacterium MRSA. In addition, these analogues exhibited activity against microbial biofilm (minimum biofilm inhibitory and eradication concentrations of 32 μg/ml and over 64 μg/ml, respectively). These data provide evidence that medusins might be promising candidates as novel antibiotic leads and that the targeted modification of a natural AMP can both improve its efficacy so as to provide new insights into antibiotic design and development.